Siyazama entrepreneurial development project: challenges of a community-university partnership within a faculty of theology - Marietjie J. Botha; Ruth M. Albertyn (Acta Theologica)
Calls for global relevance and accountability are prevalent in private-public partnerships. Current community engagement projects in higher educational institutions reflect this focus. The academic partner can play a boundary spanning (bridge building) role in a community–university partnership. The university partner often enters the partnership without full realisation of the challenges of its role. The Siyazama Craft Project, an entrepreneurial development intervention for poverty alleviation in Stellenbosch is an example of the boundary spanning role of the academic partner in the Faculty of Theology. This intervention is in line with the community interaction policy of the faculty and the university. The Siyazama entrepreneurship project is described, and challenges experienced during the course of planning, implementation and evaluation are presented. Identification of challenges in projects of this nature could provide insight for university partners in development projects. Findings could be applied to the broader context of public-private partnerships, which form part of corporate social responsibility projects in response to needs for relevance, accountability and responsible sustainable development.